A continental assessment of diurnality in frog calling behaviour. (13th October 2020) - Callaghan, Corey T.; Rowley, Jodi J. L.
Abstract: Acoustic signalling is evolutionarily important, influencing sexual selection and serving as a premating isolation mechanism. There is a strong evolutionary basis for acoustic signalling to occur nocturnally across many terrestrial vertebrate groups including mammals, reptiles and amphibians. Within some of these groups, there is a general assumption that 'most taxa are nocturnal' in their acoustic signalling, and this is a particularly strongly held view for most frogs. Here we challenge this well‐accepted notion by quantifying diurnal calling behaviour in Australian frogs, leveraging a continental‐wide citizen science dataset. Of 196 species present in the citizen science dataset, 140 (71%) were recorded at least once during the day. Of the most commonly observed species (i.e. species with at least 150 calls recorded in the database), there were surprisingly high rates of diurnal calling: 14 species had >25% of their calls recorded during the day. We also found that the relative rate of diurnal calling in frogs showed a strong phylogenetic signal, suggesting that the plasticity in calling behaviour as it relates to time of the day is strongly evolutionarily conserved. Our results highlight a suite of ecological and evolutionary questions that are worthy of further investigation.